A pan-cancer analysis of the oncogenic role of zinc finger protein 419 in human cancer - Zhu, Weizhen; Feng, Dechao; Shi, Xu; Li, Dengxiong; Wei, Qiang; Yang, Lu (Frontiers in Oncology, 2022)
Background: As a ferroptosis-related gene, the polymorphism of zinc finger protein 419 (ZNF419) at the splice donor site may generate renal cell carcinoma-associated novel minor histocompatibility antigen ZAPHIR. However, the role of ZNF419 in prognosis and immunology in human tumors remains largely unknown. This study aimed to visualize the prognostic landscape of ZNF419 at pan-cancer level and explore the relationship between ZNF419 expression and the tumor immune microenvironment. Method: Pan-cancer and mutation data were downloaded from TCGA databases and analyzed through R (version 3.6.4) and its suitable packages. Differential ZNF419 expression and prognosis were analyzed. Correlations with ferroptosis-related genes, pathway analysis, tumor stemness, heterogeneity, mutation landscape, and RNA modifications were also explored. The relationships between ZNF419 expression and tumor immunity were investigated through the TIMER and ESTIMATE methods. Result: ZNF419 was differentially expressed between tumor and normal samples and was associated with overall survival, disease-specific survival and progression-free interval for STES, KIRC, LIHC, LUSC, PRAD, and BLCA. We found the interaction between ZNF419 and FANCD2 might involve in ferroptosis in pan-cancer level. In addition, the mutation frequencies of STES, KIRC, LIHC, LUSC, PRAD, and BLCA were 1.5%, 0.3%, 0.3%, 1.9%, 0.2%, and 0.7%, respectively. We detected that the expression of ZNF419 was closely correlated with most immune checkpoint genes and immune regulatory genes. Furthermore, we found that the ZNF419 expression level was negatively related to the immune score in the six cancers mentioned above. The expression of ZNF419 was significantly associated with various infiltrating immune cells, such as CD4+ T cells, CD8+ T cells, and macrophages in patients with KIRC, PRAD, and LUSC but was only significantly related to macrophages in BLCA patients. Conclusion: ZNF419 might serve as a potential prognostic and immunological pan-cancer biomarker, especially for KIRC, LIHC, LUSC, PRAD, and BLCA.